Secure data transaction and data analysis of IOT devices using blockchain - Muhtasim, Md. Adib; Fariha, Syeda Ramisa; Islam, Nabila; Rashid, Rayhan (BRAC University, 2018)
Cataloged from PDF version of thesis report.